Another agent for PCOS‐associated infertility. Issue 2 (February 2015) - Sauereisen, Sandra
Abstract : N/A: Legro RS, Brzyski RG, Diamond MP, et al. Letrozole versus clomiphene for infertility in the polycystic ovary syndrome. N Engl J Med . 2014; 371(2):119–129.